Brand Equity Determinants and Consumers Choices of Smartphone: A Case of Iphone’s Users in Kuala Lumpur - Arman Hj. Ahmad malay; Nurul Faritsha Adiba Abdul Harith; Muhammad Zulzharfan Zulfakar; Hanneysah Sanin; Rizal Ula Ananta Fauzi (Cita konsultindo, 2022)
With the rapid development and innovation of Smartphone technologies, consumers are becoming fussy and selective in choosing their Smartphones. Most consumers only have chosen a high quality of branded Smartphones which they believe have high Brand Equity. Apple, a Smartphone brand that currently dropped from the second to the third biggest market share before Samsung and Huawei brand is one of the top three trusted brands of Smartphones in Malaysia that consumers believed to have high Brand Equity. This paper focused on Apple due to the drop in its market shares in Malaysia by conducting further investigation on its brand equity against consumer choices, particularly on its iPhone. The investigation focused on the consumers’ choices against Brand Equity and all its four determinants which are Brand Loyalty, Brand Trust, Brand Awareness, and Brand Image. 115 smartphone users (samples) were conveniently recruited in Kuala Lumpur and all questionnaires were successfully handed out to every one of them. Data collected were analyzed using SPSS. Surprisingly, the hypotheses for the test of the causal relationship between the antecedents of brand equity and consumer choice are found to be significant. Besides the dropped in Apple’s market share in Malaysia, most Smartphone users believed that Apple still has high brand equity. This research able to give a clear insight into the factors that influence brand equity simultaneously reveal the impact on the consumers’ choices towards Apple smartphones and it will help in reaching out to more consumers particularly for Apple and other Smartphone producers